The Relevance and Prospects of Using Hydroponic Technologies in Modern Conditions - Maftunaxon, Bakhodirova (American Journal of Botany and Bioengineering, 2026)
This article is devoted to analyzing the results of growing plants using hydroponic technology. It examines the essence of the hydroponics method and describes the process of cultivating berry plants using strawberries as an example. It also compares traditional, modern soil-based, and soil-less methods of growing plants. Currently, hydroponics is widely used both by amateurs and in professional plant growing. Thanks to the control of pH, electrical conductivity, and nutrient solution composition, plants receive the necessary elements in a timely manner at all stages of development — from the initial stage of growth to the formation of the crop. The advantages of the hydroponic method include the absence of the need for pesticides and herbicides, since plants in optimal conditions demonstrate high resistance to diseases and provide higher productivity compared to soil cultivation.